Learning English through poetry for EFL students - Utami, I G A Lokita Purnamika (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Poetry can help students become more sensitive to language. However, in an EFL situation, students may object to learning poetry. Thus, English teachers should know how to use poetry in their teaching. Teachers should also ensure that EFL learners do not feel worried about understanding poetry, as not all poems are difficult. Moreover, what matters most is learning English through poems rather than learning about the poems themselves. In short, it is suggested that EFL teachers encourage learners to explore poems and write their own. Poetry provides abundant language exposure that improves students’ language sensitivity and creativity in using English.